고도근시환자에서 표층황반원공에 대한 유리체절제술의 효과 - 김희원(Hee Weon Kim); 추헌구(Hun Gu Choo); 성산(San Seong); 오현섭(Hyun Sub Oh); 유용성(Yong Sung Yoo); 김순현(Soon Hyun Kim); 권오웅(Oh Woong Kwon) (Daihan angwa haghoi jabji, 2019)
목적: 고도근시환자의 표층황반원공에 대한 수술적 치료의 효과에 대해 알아보고자 하였다. 대상과 방법: 고도근시환자 중 표층황반원공으로 23게이지 유리체절제술을 시행받은 31명 31안을 대상으로 후향적으로 분석하였다. 고도근시에 해당되지 않은 환자 중 표층황반원공으로 수술받은 32명 32안을 대조군으로 설정하였으며, 최대교정시력, 빛간섭단층촬영을 이용한 표층황반원공의 구조적 변화를 수술 전, 수술 후 6개월, 12개월, 24개월째마다 비교 분석하였다. 결과: 고도근시군과 대조군은 술 전 최대교정시력과 중심구역황반두께에서 통계학적으로 유의한 차이를 보였다. 1차 수술 성공률은 고도근시군에서 96.77%, 대조군에서 100%의 성공률을 보였다. 술 후 24개월째 고도근시군은 대조군에 비해 통계학적으로 유의하게 불량한 최대교정시력을 보여주었으며, 중심구역황반두께, 표층황반원공의 내측 직경과 외측 직경에서 유의한 차이를 보였다. 고도근시군에서 중심와층간분리가 동반되어 있거나 -8.0디옵터 이상인 초고도근시안에서는 술 후 최대교정시력의 유의한 호전을 보이지 않았다. 결론: 고도근시안에서 동반된 표층황반원공에 대한 수술적 치료는 우수한 수술성공률을 보이나, 비고도근시안에 비해서 통계학적으로 불량한 결과를 보였다. 고도근시에서 표층황반원공은 술 전 시력과 황반 구조가 보존되어 있을 때 조기 수술적 치료를 고려해 볼 수 있다. Purpose: To evaluate the efficacy of surgical treatment for a lamellar macular hole in highly myopic patients. Methods: We retrospectively analyzed 31 eyes of 31 patients with a high myopia, who underwent 23-gauge vitrectomy and inner limiting membrane peeling after diagnosis of a lamellar macular hole. Thirty-two eyes of 32 patients with no high myopia were selected as the control group. The best-corrected visual acuity (BCVA) was checked and optical coherence tomography was used to evaluate structural changes in the lamellar macular hole before surgery, 6 months, 12 months, and 24 months after surgery. Results: The high myopia group and the control group showed statistically significant differences between preoperative BCVA and central foveal thickness. The success of primary surgery was 96.77% in the high myopia group and 100% in the control group. At postoperative 24 months, the high myopia group showed significantly poorer BCVA, and a statistically significant difference in the central foveal thickness and the inner and outer diameters of the lamellar macular hole. In cases of foveoschisis or a very high degree of myopia of more than -8.0 diopters, there was no significant improvement in BCVA after surgery. Conclusions: Surgical treatment of a lamellar macular hole associated with a high degree of myopia showed excellent surgical success, but was as statistically significant as surgical treatment of non-myopia eyes. Early surgical treatment can be considered for a lamellar macular hole associated with a high degree of myopia when preoperative visual acuity and macular architecture are preserved. KCI Citation Count: 0